Dietary guidance and ileal enteroendocrine cells in patients with irritable bowel syndrome - Mazzawi, Tarek (Exp Ther Med, 2016)
The enteroendocrine cells of the ileum are stimulated by the luminal contents to release specific hormones that regulate its functions. The density of ileal enteroendocrine cells is abnormal in patients with irritable bowel syndrome (IBS), and the majority of patients with IBS associate their symptoms to the consumption of certain foodstuffs. The present study investigated the effect of dietary guidance on the enteroendocrine cells of the ileum in 11 patients with IBS. A total of 10 control subjects were also included. Each patient received three sessions of dietary guidance. Colonoscopies were performed on both controls and patients with IBS (at baseline and 3–9 months after the patients had received dietary guidance). Biopsy samples from the ileum were immunostained for all enteroendocrine cells and quantified by computerized image analysis. The densities of serotonin-immunoreactive cells in controls and in patients with IBS prior to and following dietary guidance were 35.5±5.7, 38.7±7.1 and 22.3±2.6 cells/mm(2), respectively (mean ± standard error of the mean; P=0.046); the corresponding values for PYY-immunoreactive cells were 16.7±2.8, 20.2±5.1 and 21.3±2.7 cells/mm(2) (P=0.86). These results suggest that changes in enteroendocrine cell densities in the ileum along with changes in enteroendocrine cells throughout the gastrointestinal tract may contribute to the improvement in IBS symptoms following dietary guidance.